Impact of the СOVID-19 pandemic on cancer incidence in patients undergoing cancer screening during annual health checkup (population-based study) - L. E. Valkova; A. A. Dyachenko; V. M. Merabishvili; D. V. Bogdanov; A. V. Berezin; E. F. Potekhina; M. Yu. Valkov (Сибирский онкологический журнал, 2023)
Background. During the COVID-19 pandemic, annual adult check-ups have been postponed, resulting in cancer screening disruption.The aim of the study was to evaluate changes in the incidence and stage distribution of malignancies included in the screening program during the COVID-19 pandemic using the Arkhangelsk Regional Cancer Registry (ARRC).Material and Methods. We assessed the changes of the incidence rates and stage distribution for the colon, rectum, lung, breast, cervix, uterine body, ovary, prostate and kidney cancers over the periods 2018–19 and 2020–21. Results. A total of 12354 cases with 9 cancers were selected: 6680 for the period 2018–19 and 5674 (-15.1 %) for the period 2020-21. The most significant decrease in crude and age-standardized incidence rates was registered in patients with lung (-18.0–18.1 %), rectum (-25.1–25.9 %) and cervix (-33.6–36.9 %) cancers, p<0.001. The decrease was not signifcant in patients with breast, uterine body, and kidney cancers. The proportion of patients with stage I decreased in lung cancer (-20.0 %, from 14.8 % to 11.8 %), rectum (-20.2 %, from 20.9 % to 16.7 %), and uterine cervix (-37.1 %, from 53.2 % to 33.5 %). In prostate and kidney cancers, the proportion of patients with stage I increased by 30 % (from 19.5 % to 25.4 %) and 17.6 % (from 45.9 % to 54.0 %), respectively. A signifcant reduction in the proportion of early stages during the COVID-19 pandemic was observed in lung and cervical cancer. Conclusion Postponed health checkups due to COVID-19 pandemic disruptions have led to substantial reductions in new cancers being diagnosed, mainly for cervical, lung, colon and rectal cancers. No signifcant changes were observed for other cancers. Further analysis of mortality and survival of cancer patients is required. Key words: health checkup, cancer screening, COVID-19 pandemic, cancer incidence, stage distribution>˂0.001. The decrease was not significant in patients with breast, uterine body, and kidney cancers. The proportion of patients with stage I decreased in lung cancer (-20.0 %, from 14.8 % to 11.8 %), rectum (-20.2 %, from 20.9 % to 16.7 %), and uterine cervix (-37.1 %, from 53.2 % to 33.5 %). In prostate and kidney cancers, the proportion of patients with stage I increased by 30 % (from 19.5 % to 25.4 %) and 17.6 % (from 45.9 % to 54.0 %), respectively. A significant reduction in the proportion of early stages during the COVID-19 pandemic was observed in lung and cervical cancer.Conclusion. Postponed health checkups due to COVID-19 pandemic disruptions have led to substantial reductions in new cancers being diagnosed, mainly for cervical, lung, colon and rectal cancers. No significant changes were observed for other cancers. Further analysis of mortality and survival of cancer patients is required.